2010
DOI: 10.1007/s10802-010-9401-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Perceived Parent-Child Relationship Quality and Depressive Symptoms in Adolescence

Abstract: This longitudinal study examined bidirectional paths between perceived parent-adolescent relationship quality and depressive symptoms, as well as the moderating role of sex, age, and personality type. 1313 Dutch adolescents (51% girls) from two cohorts (923 12-year olds and 390 16-year olds at Wave 1) reported on their personality, depressive symptoms, and perceived relationship quality to parents in four waves. Consistent with a relationship erosion perspective, depressive symptoms negatively predicted percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
268
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(310 citation statements)
references
References 58 publications
(79 reference statements)
34
268
3
5
Order By: Relevance
“…Branje et al, 2010;, girls reported higher levels of companionship, disclosure and support in their relationship with their mothers than boys, suggesting that girls are more inclined to use their mothers as their primary source of parental support. This provides partial support for previous research suggesting that young people generally identify with their samesex parent more than their opposite-sex parent (Starrels, 1994).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Branje et al, 2010;, girls reported higher levels of companionship, disclosure and support in their relationship with their mothers than boys, suggesting that girls are more inclined to use their mothers as their primary source of parental support. This provides partial support for previous research suggesting that young people generally identify with their samesex parent more than their opposite-sex parent (Starrels, 1994).…”
Section: Discussionmentioning
confidence: 91%
“…It may be that the lack of social support resulting from being excluded increases distress levels in young people. However it is important not to assume causation; it may be that adolescents with mental health difficulties overburden friends with problems and drive them away or else may lack the interpersonal competence to maintain close friendship (Branje et al, 2010;Buhrmester, 1990 As hypothesised, boys reported higher levels of negative qualities in their romantic relationships than girls. Specifically, they reported experiencing higher levels of dominance and pressure in these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the majority of our sample is female (93.4%), and there is research suggesting that intergenerational transmission of depression may differ depending on the gender of the parent (Branje et al, 2010). We found no significant differences between total or individual item DISP scores for mothers and fathers in our sample.…”
Section: Discussionmentioning
confidence: 55%
“…For example, there are evidences which suggested that females are more vulnerable to inter-parental conflict than males (Cummings & Davies, 2011;Gore, Aseltine, & Colten, 1993;Unger, Brown, Tressell, & McLeod, 2000). However, there are also counter arguments which claimed that males are at greater risk for maladjustment than females following parental divorce (Branje, Hale, Frijns, & Meeus, 2010;Brown & Portes, 2006). Nevertheless, some other studies found no moderation effect (Caples & Barrera, 2006;Eberhart, Shih, Hammen, & Brennan, 2006).…”
Section: Mechanism Affecting Attitudes Towards Marriage Among Adolescmentioning
confidence: 99%